2018
DOI: 10.5123/s1679-49742018000200017
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento Rápido de Vacinação na prevenção do sarampo no estado do Ceará, em 2015

Abstract: Measles vaccination campaigns enabled the immunization coverage goal in the State of Ceará to be surpassed, despite the considerable number of unvaccinated children found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
0
8
0
10
Order By: Relevance
“…SI-PNI enables quantitative analysis of vaccination coverage by vaccine type, doses given, and dropout rate throughout the country by age group, time, and geographical area (Assis Moura et al, 2018). Within SI-PNI, it is also possible to perform monthly follow-up of vaccination activities regarding the quantity of distributed and applied doses, coverage, and adverse events post-vaccination (EAPV).…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…SI-PNI enables quantitative analysis of vaccination coverage by vaccine type, doses given, and dropout rate throughout the country by age group, time, and geographical area (Assis Moura et al, 2018). Within SI-PNI, it is also possible to perform monthly follow-up of vaccination activities regarding the quantity of distributed and applied doses, coverage, and adverse events post-vaccination (EAPV).…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“….052 casos da doença41 . Após sucessivas ações de vigilância e imunizações, em 2016, o Brasil recebeu o certificado de eliminação da circulação do vírus do sarampo pela OMS, declarando a região das Américas livre do sarampo39 .Desde janeiro de 2018, foram verificados surtos de sarampo nos estados de Roraima e Amazonas, contabilizando, até o mês de junho de 2018, 314 casos39 .…”
unclassified
“…Differently to what happened in the state of Ceará, a study conducted in the state of Pará about the measles outbreak found that the high rates of vaccination coverage achieved through routine vaccination or previous campaigns contributed to containing the outbreak in that region, given that few doses were administered during the outbreak and lockdowns and intensified actions were targeted. 9 After 20 weeks of the epidemic, in September 2015, the state of Ceará declared that measles virus transmission had been interrupted. It is important to note that, in the state as a whole, the majority of the population aged between 6 months and 29 years old had not been vaccinated against measles.…”
Section: Discussionmentioning
confidence: 99%
“…1 The reemergence of the epidemic points to the continuing challenge of promoting (i) epidemiological surveillance that is receptive to and adequate for detecting suspected cases, (ii) active tracing by health teams of suspected and/or confirmed cases at silent health units, and (iii) awareness raising of public and private health service workers with regard to compulsory notification being obligatory. 9 In recent years the National Immunization Program has made considerable progress, including with its Information System. This system enables the vaccines administered to each individual to be recorded, as well as their origin, thus permitting more trustworthy assessment of this information, as well as aiding vaccination coverage estimates, the impact of which can go beyond the administrative sphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation